The paradoxical meeting of depth psychology and physics reflections on the unification of psyche and matter - Matthews, Robert Samuel (Routledge, Taylor & Francis Group, 2022)
"This book unites the worlds of physics and depth psychology through analysis of carefully selected existing and new dream materials. Their interpretation by Matthews provides fertile ground for the unifying of the extreme opposites of psyche and matter and forms a continuation of the deep dialogue between acclaimed psychologist Carl Jung and Nobel physicist Wolfgang Pauli. What emerges is an individuation process where inner and outer worlds are intertwined through a succession of dream images, culminating with that of the ring i, the mathematical function at the heart of quantum physics. This mysterious function unites wave and particle and symbolically carries the quality of paradox. The occurrence of the ring i in Pauli's and the author's dreams suggests paradox is a necessary psychological state to experience a living union between psyche and matter. Analysis of accompanying materials further indicates the arising of a new world view where inner and outer, mind and matter, may again be seen as a unified whole. This book is an engaging read for academics and researchers in the field of Jungian psychology and will appeal to those interested in the novel application of quantum physics to philosophy, psychology and spirituality"--
Keywords: Tiefenpsychologie; Physik; Psychology / Philosophy; Physics / Psychological aspects; Subconsciousness; Jungian psychology; Unconscious, Psychology; Psychologie / Philosophie; Physique / Aspect psychologique; Inconscient; Psychologie analytique